A thematic analysis of preservice teachers’ peer feedback in teacher education - Eunjeong Park (English Language Teaching Educational Journal, 2026)
Peer feedback plays a key role as a way of encouraging reflective practice and professional learning in teacher education, but there is less understanding about how preservice teachers assess the instructional quality influenced by evaluative orientations. In this qualitative research, the researcher seeks to know the themes of peer feedback given by preservice English teachers after instructional activities. Thematic analysis was applied to the peers’ evaluative comments to determine common criteria that were used to construct the teaching effectiveness. There were three themes: (1) the focus on the relevance of the topic to the learners, (2) the importance of interactions and discussion-based activities, and (3) the lack of interest in linguistic scaffolding and pedagogical rigor. These findings show that peer feedback primarily indicates adherence to the principles of communicative language teaching, particularly learner-centeredness and interaction but does not pay sufficient attention to linguistic rigor and learning outcomes. Through the lenses of second language acquisition and teacher education, the findings imply that even though preservice teachers show conceptual approval of communicative pedagogy, they need more assistance in the creation of evaluative literacy that relates the engagement-based practices to the process of language learning and teaching. This study adds to existing literature on peer feedback in teacher education by pointing out the necessity of systematic instructions in peer evaluation practices.